CARDIAC & PULMONARY COMPLICATIONS SEEN IN LIVER CIRRHOSIS-AN OBSERVATIONAL STUDY AT A TERTIARY CARE HOSPITAL (Indian Journal of Applied-Basic Medical Sciences, 2020)
INTRODUCTION: Cirrhosis is a condition that is defined histopathologically and has a variety of clinical manifestations and complications, some of which can be life-threatening. Patients with cirrhosis and portal hypertension exhibit characteristic cardiovascular & pulmonary hemodynamic changes. The cardiovascular complications include systolic dysfunction, diastolic dysfunction & electrochemical abnormalities like prolonged QT interval in Electrocardiogram (ECG), and Respiratory complications include Consolidation, Pleural Effusion & Pulmonary Arterial Hypertension, which may be due to Hepatopulmonary or Portopulmonary syndrome STUDY DESIGN: A two-year prospective observational study was conducted from July,2014 to June 2016 AIM: To study the different cardiac and pulmonary complications in the patients of Liver Cirrhosis. MATERIALS & METHODS: A two-year prospective observational study was conducted from July,2014 to June 2016 at a tertiary care hospital in Ahmedabad, Gujarat, India, including 30 patients (>12 years old), who were known cases of cirrhosis of liver as well as those newly diagnosed with it, with cardiopulmonary complications, developed after liver cirrhosis, in the absence of other etiological factors. Clinical profile with laboratory studies and diagnostic tests were studied. RESULTS: This study showed that cardiopulmonary complications in cirrhotic patients are more frequently seen in males than females, which commonly manifest during third & fourth decade. Dyspnoea is the most common symptom seen in the study. Among the pulmonary complications, Pneumonia & Hydrothorax are more common compared to hepatopulmonary & portopulmonary syndromes, and among cardiac complications, Diastolic dysfunction is a major complication in such patients, which increases with increasing severity of cirrhosis, as indicated by CP score. CONCLUSION: Among these patients, Cardiac and pulmonary complications have nearly the same incidences.
Keywords: histopathologically; dysfunction; electrochemical